Assessment of the influence of the time spent by vehicles at the stopping point of urban passenger transport on the level of conflict in the interaction of the route flow - Vdovychenko, Volodymyr (Technology audit and production reserves, 2020)
The object of research is the effect of the time spent by vehicles at the stopping point on indicators of the level of conflict in the interaction of the route flow. As a controlled parameter that determines the level of reserve capacity of the stopping point and reproduces the characteristic effect on the conflict of interaction, the additional service downtime of vehicles is allocated. Simulation and statistical processing of the results are used, which allow to establish typical types of patterns for stopping points with different intensities of the input route flow. It has been established that for stopping points with low and medium intensity (up to 40 vehicles/h), the reserve of throughput has an inverse linear dependence on the service time and for exponentials with high intensities (more than 40 vehicles/h) it is exponential. Changing the reserve of bandwidth by setting a rational service idle duration allows to affect the number of conflicts and the length of time in the queue. This makes it possible to determine its acceptable values for the corresponding intensity level of the route flow. Based on the conducted experimental studies, it is established that an additional service downtime for a stopping point with intensity of up to 40 vehicles is an acceptable duration of up to 40 s. With the introduction of more than 125 s – in 71.2% of the incoming stream, conflict situations will be observed. From the position of minimizing the conflict of interaction between stopping points with an input route flow intensity of more than 40 vehicles/h, the introduction of an additional service downtime is not at all possible. Establishing dependence is the methodological basis for the formation of elements of a management decision support system based on an analysis of the impact of vehicle downtime on the conflicting interaction of the route flow. They introduce certain orderliness in the processes of planning the work of passenger infrastructure facilities, make it possible to systematize their service-resource parameters and contribute to improving the safety of passenger transport services.